Website-Based Application Project Ordering Information System at Abercode Software House - Muhyidin Yahya; Rina Kurniawati (Jurnal E-Komtek (Elektro-Komputer-Teknik), 2022)
The rapid development of technology brings changes to all sectors. One technology that plays an important role is web-based. Abercode Software House is a company engaged in software development services. In one of the project order processing flows, the traditional method was used, namely interviews and manual notes. Therefore, a website-based Application Project Order Information System is one way to solve problems in Abercode Software House. The building of this system used software development using the Waterfall method and the PHP and HTML programming languages and MySQL as the database. The data collection method used was qualitative and data-based analysis methods and Blackbox testing methods. Based on the results of the study, it was found that the traditional method slowed down and complicated the ordering process. The testing information systems carried out with the Blackbox method obtained the expected results as a whole, with for the testing carried out directly by Abercode Software House.